1977
DOI: 10.1093/jnci/59.6.1611
|View full text |Cite
|
Sign up to set email alerts
|

Dentition, Diet, Tobacco, and Alcohol in the Epidemiology of Oral Cancer 2

Abstract: Interview and dental examination data were gathered on 584 males with cancer of the oral cavity and on 1,222 control patients with nonneoplastic diseases at Roswell Park Memorial Institute, Buffalo, New York. No dietary characteristics distinguished cancer patients from controls. However, a higher risk of developing oral cancer was associated with heavy smoking, heavy drinking, and poor dentition. When controlled for the other factors, each factor carried a higher risk. Moreover, heavy smokers and heavy drinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1
13

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(116 citation statements)
references
References 0 publications
3
96
1
13
Order By: Relevance
“…93,133 The strongest and most consistent indicator of risk in the literature was tooth loss, likely indicative of chronic poor oral health. Several studies reported elevated risk associated with any tooth loss 90,93,129,[134][135][136] and also increased risk with increased number of lost teeth. 95,137 Both smoking and alcohol drinking have significant direct effects on oral health and are strongly correlated with poor oral hygiene.…”
Section: Oral Hygienementioning
confidence: 99%
See 1 more Smart Citation
“…93,133 The strongest and most consistent indicator of risk in the literature was tooth loss, likely indicative of chronic poor oral health. Several studies reported elevated risk associated with any tooth loss 90,93,129,[134][135][136] and also increased risk with increased number of lost teeth. 95,137 Both smoking and alcohol drinking have significant direct effects on oral health and are strongly correlated with poor oral hygiene.…”
Section: Oral Hygienementioning
confidence: 99%
“…However, an independent role for oral hygiene was supported by significant elevations in oral cancer risk (approximate OR 3-9) among nonsmokers and nondrinkers with poor oral hygiene in case-control studies. 136,137 Additive 136 and multiplicative 137 risk (in which combined exposures act synergistically to either add to or multiply, respectively, the risk associated with either exposure alone) between poor oral hygiene and alcohol and tobacco use have also been observed. Quantitative and qualitative differences were found between the oral microflora of smokers, patients with oral cancer, and controls.…”
Section: Oral Hygienementioning
confidence: 99%
“…Among ''ever drinkers,'' the total number of drinks consumed per week was calculated by summing the average number of drinks of beer, wine, and hard liquor reportedly consumed per week. On an a priori basis, total alcohol consumption was dichotomized at less than seven drinks/week and seven or more drinks/week [9,23]. For subjects interviewed after April 28, 1996, the questionnaire included questions regarding whether and when the drinking of each alcoholic beverage type had been discontinued.…”
Section: Tobacco and Alcohol Usementioning
confidence: 99%
“…Other aetiological factors such as diet [46,47], oral hygiene and dentition [48,49], mouthwashes [50,51] and viral infections [52,53] have also been identi®ed but their role is inconsistent.…”
Section: Risk Factorsmentioning
confidence: 99%